Pengaruh Beban Kerja dan Budaya Organisasi Terhadap Loyalitas Karyawan Pada CV Asanka Wijaya - Saputra, Monika; Akmal, Samsul; Hidayat, Rahmat Al (Jurnal Adminitrasi Bisnis Nusantara, 2024)
In this study, the researcher aimed to investigate the effect of workload and organizational culture on employee loyalty at CV Asanka Wijaya. This is a descriptive-causal study and a quantitative research. The survey method was used with non-random sampling technique, specifically purposive sampling, to select a sample of employees. Data were collected using a Likert-scale questionnaire and analyzed using regression analysis and descriptive statistics. The statistical analysis conducted in this study was a simple linear regression, preceded by tests for validity, reliability, and classical assumptions as preliminary tests. This study indicates that workload has a partial negative effect on employee loyalty. The effect of this variable is 0.501, or 50.1%. and that organizational culture has a positive influence on employee loyalty by 0.362, or by 36.2%..